Molecular Biomarkers for Prognosis, Diagnosis, and Therapy in Hemorrhagic Stroke - Sugiyanto, Aqilla Nasywa Nabila; Evana, Nafisya Ayu; Fawaiz, Afdhila Anugerah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hemorrhagic stroke is an acute condition characterized by the rupture of blood vessels in the brain and has a high mortality rate. The bleeding leads to the formation of hematoma and perihematomal edema, which significantly worsen the patient's prognosis. Early diagnosis and management are crucial to improving clinical outcomes. In recent years, blood-based molecular biomarkers have become a major focus of research due to their potential to support diagnosis, evaluate etiology, predict hematoma growth, and assess inflammatory responses. Biomarkers such as GFAP and S100B have proven effective in distinguishing hemorrhagic stroke from ischemic stroke in the hyperacute phase. Meanwhile, β-amyloid and MMP play roles in identifying the etiology of bleeding, especially related to cerebral amyloid angiopathy. Additionally, levels of calcium, magnesium, LDL-C, and ApoE ε2 are known to be associated with the risk of hematoma expansion. Inflammatory biomarkers such as CRP, NLR, gelsolin, and CD163 reflect neuroinflammatory processes and blood-brain barrier damage that worsen secondary injury. The clinical use of these biomarkers opens opportunities for faster, more accurate, and personalized diagnostic and therapeutic approaches in hemorrhagic stroke.